A hybrid hydrazine redox flow battery with a reversible electron acceptor. Issue 33 (14th August 2018) - Varhade, Swapnil; Bhat, Zahid M.; Thimmappa, Ravikumar; Devendrachari, Mruthyunjayachari C.; Kottaichamy, Alagar R.; Gautam, Manu; Shafi, Shahid P.; Kalegowda, Yogesh; Thotiyl, Musthafa Ottakam
Abstract : The flow battery possesses outer-sphere catholyte driven by the simple carbon based electrodes with performance higher than Pt based DHFC. Abstract : Hydrazine is a pollutant with high hydrogen content, offering tremendous possibilities in a direct hydrazine fuel cell (DHFC) as it can be converted into electricity via benign end products. Due to the inner sphere nature of half-cell chemistries, hydrazine cross over triggers parasitic chemistry at the Pt-based air cathode of a state-of-the-art DHFC, overly complicating the already sluggish electrode kinetics at the positive electrode. Here, we illustrate that by altering the interfacial chemistry of the catholyte from inner sphere to outer sphere, the parasitic chemistry can be dissociated from the redox chemistry of the electron acceptor and the hybrid fuel cell can be driven by simple carbon-based cathodes. The reversible nature of an outer sphere catholyte leads to a hybrid fuel cell redox flow battery with performance metrics ∼4 times higher than a Pt-based DHFC-air configuration.